Narcolepsy patients' blood‐based miRNA expression profiling: miRNA expression differences with Pandemrix vaccination. (1st March 2017) - Mosakhani, N.; Sarhadi, V.; Panula, P.; Partinen, M.; Knuutila, S.
Abstract : Objectives: Narcolepsy is a neurological sleep disorder characterized by excessive daytime sleepiness and nighttime sleep disturbance. Among children and adolescents vaccinated with Pandemrix vaccine in Finland and Sweden, the number of narcolepsy cases increased. Our aim was to identify miRNAs involved in narcolepsy and their association with Pandemrix vaccination. Materials and methods: We performed global miRNA proofing by miRNA microarrays followed by RT‐PCR verification on 20 narcolepsy patients (Pandemrix‐associated and Pandemrix‐non‐associated) and 17 controls (vaccinated and non‐vaccinated). Results: Between all narcolepsy patients and controls, 11 miRNAs were differentially expressed; 17 miRNAs showed significantly differential expression between Pandemrix‐non‐associated narcolepsy patients and non‐vaccinated healthy controls. MiR‐188‐5p and miR‐4499 were over‐expressed in narcolepsy patients vs healthy controls. Two miRNAs, miR‐1470 and miR‐4455, were under‐expressed in Pandemrix‐associated narcolepsy patients vs Pandemrix‐non‐associated narcolepsy patients. Conclusions: We identified miRNA expression patterns in narcolepsy patients that linked them to mRNA targets known to be involved in brain‐related pathways or brain disorders.